The passway of women entrepreneurship: Starting from social capital with open innovation, through to knowledge sharing and innovative performance - Made Setinib; Ni Nyoman Kerti Yasa; I. Wayan Supartha; I G. A. Ketut Giantari; Ismi Rajiani (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Customs and culture should create women' independence to actualize themselves in an era of emerging social progress in order to lead to the domination of women in the development of creative businesses. This research examines the role of social capital and whether it becomes a supporting or hindering factor in developing the creative industry of women entrepreneurs by examining the role of information sharing and innovations. Employing purposive sampling, questionnaires were distributed to 200 women entrepreneurs, and data were analyzed by using Structural Equation Modeling(PLS-SEM)software with SmartPLS Version 3.0. Social capital has a positive influence on the business performance of women entrepreneurs in Bali, Indonesia. Thus, the beliefs and norms that exist in the social capital of the Balinese Hindu concept can filter the information obtained from various information in business, which will ultimately be utilized by women entrepreneurs to create various innovations to meet the market demand. However, opportunities for women entrepreneurs are very limited to capital due to lack of guarantees to get capital, and a lack of entrepreneurship skills in the technological era, market access, bureaucracy, and legalization. Further, managerial skills, access to information technology, as well as the perspective that the men must be superior in Balinese culture and customs, make business for women entrepreneurs limited.
Keywords: 650; innovation; knowledge sharing; social capital; women entrepreneurs